Sustainable Cultural Heritage Tourism in Bali: a Qualitative Study of Destonations - Kadek Andika Wira Prayoga; Nyoman Diah Utari Dewi; Ni Putu Tirka Widanti (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
Heritage tourism constitutes a fundamental pillar of Bali’s tourism development, contributing not only to regional economic growth but also to the preservation of cultural values and historical assets. Nevertheless, the rapid expansion of mass tourism has generated significant challenges related to cultural authenticity, sustainability, and local community involvement. This study aims to examine the implementation of heritage tourism in Bali and to analyze its impacts on cultural preservation and local community welfare. A qualitative descriptive approach was employed using a case study design across selected heritage destinations in Bali. The study involved 20 informants comprising destination managers, traditional community leaders, tourism practitioners, and tourists. Data were collected through in-depth interviews, field observations, and document analysis. The findings reveal that heritage tourism in Bali has contributed positively to the conservation of cultural heritage through site revitalization and the reinforcement of local identity. However, its implementation remains constrained by excessive commercialization and limited community participation in decision-making processes. The study concludes that sustainable heritage tourism management in Bali requires strong collaboration among government authorities, traditional communities, and tourism stakeholders. The implications of this research highlight the necessity of formulating culture-based tourism policies that prioritize heritage conservation and the empowerment of local communities to ensure long-term sustainability.Keywords: Bali, Cultural Tourism, Cultural Preservation, Heritage Tourism, Sustainable